MENJAWAB KEBUTUHAN PEKERJA MIGRAN INDONESIA BERKETERAMPILAN BAHASA INGGRIS SEBAGAI BAHASA GLOBAL - Perangin-Angin, Dalan Mehuli; Manggala, Simon A.; Fitriati, Anna; Putranti, Adventina; Rosiandani, Ni Luh Putu; Puri, Anindita D.; Pukan, Elisabeth O. (Universitas Sanata Dharma, 2023)
This paper aims to discuss the reasons and solutions why and how Indonesian Migrant Workers (IMWs), need to increase their English proficiency. We use a sociolinguistic approach to understanding the phenomenon of English as a Global Language including its history, social functions, prestige, and why its speakers gain better social status in society. Furthermore, we discuss the data we gained from dispersing questionnaires for need analysis in google forms to some networks of Indonesian in Hong Kong (59 correspondents). The data doubtlessly show they want to enhance their English mastery and intend to join our free online English course program. In the second year of the program (2022), we become more convinced in conducting the program for a longer run in the future, as unexpectedly the number of IMWs who want to join the course has raised four times (about three hundred from the expected ninety participants only), and have gained supports from various institutions such as the Consulate General of the Republic of Indonesian in Hong Kong and Macau, and Indonesian Diaspora Network Global. As an academic institution, we are assured that the present program will be a valuable contribution for society, especially the IMWs.